Common Trends in Frameworks for Analyzing Intercultural Content in Language Teaching Course Books - Chau Thi Hoang Hoa (IGI Global, 2024)
The growing number of studies on how culture and what types of culture should be included in EFL education entails the existence of several frameworks for intercultural content analysis. This chapter undertakes a systematic review of analytical frameworks employed in 28 pertinent studies published within the last 15 years. The findings propose three common trends in classifying intercultural content, based on (1) socio - geographical distribution of English use, (2) the nature of language and culture education, and (3) the depth of intercultural interaction involved. Among these, frameworks grounded in the socio-geographical distribution of the English language are notably prevalent. Also, the study revealed that combining multiple frameworks for the analysis of intercultural content is commonly practiced. This review aims to increase educators' awareness of the presence of intercultural aspects in language teaching. Finally, it seeks to fill the gaps in existing literature by addressing the categorization and trends in the application of intercultural content analysis.